2021
DOI: 10.3390/ijms22031325
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Notch Signaling for Bone Metabolism and Regeneration

Abstract: Notch1-4 receptors and their signaling pathways are expressed in almost all organ systems and play a pivotal role in cell fate decision by coordinating cell proliferation, differentiation and apoptosis. Differential expression and activation of Notch signaling pathways has been observed in a variety of organs and tissues under physiological and pathological conditions. Bone tissue represents a dynamic system, which is constantly remodeled throughout life. In bone, Notch receptors have been shown to control rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 119 publications
1
42
0
Order By: Relevance
“…Tissue regeneration is a complex process involving multiple cell types and various signaling pathways. The signaling pathways involved in tissue regeneration mainly include WNT [ 59 ], FGF [ 60 ], IGF [ 61 ], BMP [ 62 ], Notch [ 63 ], Hippo [ 64 ], Hedgehog [ 65 ], and VEGF [ 66 ]. The cell types involved in regeneration depend on the type of regenerating tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue regeneration is a complex process involving multiple cell types and various signaling pathways. The signaling pathways involved in tissue regeneration mainly include WNT [ 59 ], FGF [ 60 ], IGF [ 61 ], BMP [ 62 ], Notch [ 63 ], Hippo [ 64 ], Hedgehog [ 65 ], and VEGF [ 66 ]. The cell types involved in regeneration depend on the type of regenerating tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hMSCs have the potential to differentiate into different lineages, including osteoblasts (bone), neuroblasts (neural tissue), adipoblasts (fat), myoblasts (muscle), and chondroblasts (cartilage) 3 , 4 . In particular, osteogenic induction of hMSCs differentiation in conjunction with tissue engineering approaches has been exploited to provide an alternative method besides autologous bone graft to replace or restore damaged bone tissues 5 . This evidence demonstrates the application of hMSCs as a promising cell source in bone tissue engineering, given their regenerative properties.…”
Section: Introductionmentioning
confidence: 99%
“…Notch signaling is an evolutionarily conserved, intercellular, and contact-dependent signaling pathway which regulates cell fate decisions and plays a significant role during development and organogenesis [5][6][7][8][9][10]. Many studies have demonstrated the critical role of Notch signaling in cell fate determination, cell proliferation, differentiation, and apoptosis in various cell types [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%